2022
DOI: 10.1007/s12011-022-03193-8
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Tauroursodeoxycholic Acid and 4-Phenylbutyric Acid on Selenium Distribution in Mice Model with Type 1 Diabetes

Abstract: The effect of selenium on diabetes is significant. As pharmaceutical chaperones, tauroursodeoxycholic acid (TUDCA) and 4-phenylbutyric acid (4-PBA) can effectively improve the oxidative stress of the endoplasmic reticulum. This study established a mice model with type 1 diabetes (T1D) to evaluate the effects of pharmaceutical chaperones on selenium distribution. Streptozotocin was used to induce Friend virus B-type mice to establish a T1D mice model. Mice were administered with TUDCA or 4-PBA. Selenium levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It was reported that 4-PBA could alleviate hyperoxia-induced acute lung injury 89 and rescue hyperoxaluria-induced nephrolithiasis by modulating urinary glycoproteins. 90 In addition, TUDCA and 4-PBA have crucial effects on selenium distribution in diabetic mice 91 and they also block ER stress in post-ischemic kidneys. 92 Moreover, a study of gut microbial dysbiosis and plasma metabolic in vitiligo detected an abnormal level of TCDCA, an upstream metabolite of TUDCA.…”
Section: Clinical Treatmentsmentioning
confidence: 99%
“…It was reported that 4-PBA could alleviate hyperoxia-induced acute lung injury 89 and rescue hyperoxaluria-induced nephrolithiasis by modulating urinary glycoproteins. 90 In addition, TUDCA and 4-PBA have crucial effects on selenium distribution in diabetic mice 91 and they also block ER stress in post-ischemic kidneys. 92 Moreover, a study of gut microbial dysbiosis and plasma metabolic in vitiligo detected an abnormal level of TCDCA, an upstream metabolite of TUDCA.…”
Section: Clinical Treatmentsmentioning
confidence: 99%
“…The relation of selenium and diabetes is controversial, but a study showed that selenium helps in reducing diabetes because it exhibits antioxidant and anti-inflammatory properties [48,49]. Besides reducing the oxidative stress, TUDCA showed a promising result in the selenium distribution in the liver, kidney, heart, and muscle of type 1 diabetic mice, and was also found to be effective in blood glucose levels of mice [50]. These studies concluded that TUDCA is a potential therapeutic agent for the protection of beta cells as well as in insulin stimulation [51].…”
Section: Tauroursodeoxycholic Acid (Tudca)mentioning
confidence: 99%